Distrofias musculares progressivas de cinturas tipo 2 : perfil epidemiológico no estado do Ceará - Pimentel, Leonardo Halley Carvalho (2008)
To report the clinical and muscle biopsy findings from the recessive forms of limb girdle muscular dystrophies (LGMD type 2) seen in the state of Ceará, Northeast of Brazil. Design: Case series. Setting: Tertiary care clinic, University hospital. Patients and Methods: We studied 41 patients from 32 families with chronic progressive weakness in a limb-girdle distribution seen at a tertiary care hospital. All patients were born in the State of Ceará. Patients with autossomal dominant pattern or facial involvement were excluded. Muscle biopsies specimens were immunostained for dystrophin, sarcoglycan, dysferlin, myotilin, merosin and emerin on all cases. Results: We found a specific protein deficiency in 24 patients (58.5%) from 20 families. Among these patients 11 (45.8%) had sarcoglycanopathy and 13 (54.2%) had dysferlinopathy and the pattern of inheritance was autosomal recessive or sporadic. Eletrocardiographic changes were seen in 6 (54.5%) patients with sarcoglycanopathy. Conclusion: Sarcoglicanopathies and disferlinopathies represent more than 60% of the cases of families with LGMD type 2 in this series from Northeast Brazil. Immunohistochemistry is still a very important tool for classification of LGMDs if genetic testing is not available or limited. Further studies are necessary to characterize the genetic background of the different LGMD families and to further characterize the other subtypes of LGMD type 2 in Brazil.